Associação de SNPs em genes candidatos e de regiões cromossômicas com espessura de gordura subcutânea em bovinos da raça Canchim - Veneroni, Gisele Batista (Universidade Federal de São Carlos, 2010)
The Canchim has been used in beef cattle as an alternative to production intensification. Canchim (5/8 Charolais + 3/8 Zebu) and MA (offspring of Charolais bulls and 1/2 Canchim + 1/2 Zebu cows) constitute a synthetic beef cattle breed which has a good growth potential and tropical adaptation but suboptimal fat deposition under pasture. Backfat thickness (BF), total fat amount and distribution of fat have a strong impact on carcass and meat quality in beef cattle. For this reason, research has been conducted to increase fat deposition in this breed, including the search for molecular markers to identify animals with high genetic potential for fat deposition. To incorporate molecular genetics into breeding programs in beef cattle, it is essential that the association between molecular markers and production traits is evaluated in the population in which they are to be used. There are reports of many candidate genes and chromosomal segments associated with variation in fat deposition in cattle. The objective of this study was to identify SNPs associated to backfat thickness in Canchim. To achieve this objective we searched for SNPs in development and differentiation enhancing factor 1 and insulin-like growth factor binding protein 3 genes, tested the association of SNPs in the insulin-like growth factor binding protein 3, peroxisome proliferative active receptor gamma coactivator 1A, proteasome 26S subunit ATPase 1, development and differentiation enhancing factor 1, corticotropin releasing hormone and fatty acid binding protein 4 genes with fat thickness in Canchim and MA beef cattle. We also analyzed the existence of genomic regions associated with backfat thickness in these populations using a 54 K chip in extreme phenotypes. From the associated regions we selected the ones of BTA14 to validate the association by analysis of haplotypes in the whole population. The SNPs analyzed in development and differentiation enhancing factor 1 and fatty acid binding protein 4 genes were associated with variation in backfat thickness, wereas no association was found for the SNPs of the insulin-like growth factor binding protein 3, peroxisome proliferative active receptor gamma coactivator 1A, proteasome 26S subunit ATPase 1 and corticotropin releasing hormone genes. Additionally, two chromosomal regions of BTA14 were associated with the trait in this work.
Keywords: Biologia molecular; Marcador molecular; Gordura subcutânea; Bovino de corte; Genes candidatos; Chip de alta densidade de SNPs; Canchim; Espessura de gordura subcutâne; Candidate genes; High density SNPs chip; Canchim; Backfat thickness; CIENCIAS BIOLOGICAS::GENETICA